CELIBACY IN EARLY JUDAISM - van der Horst, Pieter W. (Revue biblique, 2002)
It is commonly assumed that celibacy is a Christian ideal that was inspired by Greek philosophical concepts and that in Judaism the first commandment in the Bible (Gen. 1:28 "Be fruitful and multiply") has prevented the unmarried status from becoming an ideal. In this article it is argued that, in spite of this biblical commandment, in some circles of ancient Judaism celibacy did become an ideal. All relevant Jewish sources are discussed (Essenes, Therapeutae, Bannus, Simeon ben Azzai, John the Baptist, Jesus) and it is argued that this material has to be taken into account in the study of the development of early Christian asceticism. Le célibat est considéré comme un idéal chrétien inspiré de notions philosophiques grecques; dans le judaïsme, le premier commandement de la Bible (Gn 1, 28 « Soyez féconds et multipliez-vous ») l'aurait empêché d'être un idéal. L'argumentation de l'article est que, dans certains cercles du judaïsme ancien, en dépit du commandement biblique, le célibat fut érigé en idéal. Toutes les sources juives concernées sont discutées (Esséniens, Thérapeutes, Bannus, Siméon Ben Azzai, Jean le Baptiste, Jésus), et on soutient que ces éléments doivent êre pris en compte dans l'étude de l'émergence de l'ascétisme chrétien primitif.